Methylated free‐circulating HPP1 DNA is an early response marker in patients with metastatic colorectal cancer. Issue 9 (22nd February 2017) - Herbst, Andreas; Vdovin, Nikolay; Gacesa, Sanja; Philipp, Alexander; Nagel, Dorothea; Holdt, Lesca M.; op den Winkel, Mark; Heinemann, Volker; Stieber, Petra; Graeven, Ullrich; Reinacher‐Schick, Anke; Arnold, Dirk; et al.
Abstract : Detection of methylated free‐circulating DNA (mfcDNA) for hyperplastic polyposis 1 ( HPP1) in blood is correlated with a poor prognosis for patients with metastatic colorectal cancers (mCRC). Here, we analyzed the plasma levels of HPP1 mfcDNA in mCRC patients treated with a combination therapy containing a fluoropyrimidine, oxaliplatin and bevacizumab to test whether HPP1 mfcDNA is a suitable prognostic and response biomarker. From 467 patients of the prospective clinical study AIO‐KRK‐0207, mfcDNA was isolated from plasma samples at different time points and bisulfite‐treated mfcDNA was quantified using methylation specific PCR. About 337 of 467 patients had detectable levels for HPP1 mfcDNA before start of treatment. The detection was significantly correlated with poorer overall survival (OS) (HR = 1.86; 95%CI 1.37–2.53). About 2–3 weeks after the first administration of combination chemotherapy, HPP1 mfcDNA was reduced to non‐detectable levels in 167 of 337 patients. These patients showed a better OS compared with patients with continued detection of HPP1 mfcDNA (HR HPP1 (sample 1: pos/ sample 2: neg) vs. HPP1 (neg/neg) = 1.41; 95%CI 1.00–2.01, HPP1 (neg, pos/pos) vs. HPP1 (neg/neg) = 2.60; 95%CI 1.86–3.64). Receiver operating characteristic analysis demonstrated that HPP1 mfcDNA discriminates well between patients who do (not) respond to therapy according to the radiological staging after 12 or 24 weeks (AUC = 0.77 or 0.71, respectively). Detection of HPP1 mfcDNA can be used as a prognostic marker and an early marker for response (as early as 3–4 weeks after start of treatment compared with radiological staging after 12 or 24 weeks) to identify patients who will likely benefit from a combination chemotherapy with bevacizumab. Abstract : What's new? Tumor cells of primary tumors and metastases are constantly turned over with their DNA being released into blood circulation. Here the authors quantified circulating DNA of the hyperplastic polyposis 1 (HPP1) gene, which is frequently methylated in colorectal tumors, in a prospective clinical study of combination chemotherapy in patients with metastatic colorectal cancer. They confirmed their previous finding that HPP1 methylated free‐circulating DNA (mfcDNA) is a prognostic marker for progression‐free and overall survival in these patients. In addition, HPP1 mfcDNA served as a marker differentiating between chemotherapy responders and non‐responders, underscoring the usefulness of DNA‐based biomarkers in cancer treatment.